Experimental Study on Temperature Field Evolution Mechanism of Artificially Frozen Gravel Formation under Groundwater Seepage Flow - Tian-liang Wang; Fei Zhang; Yang Wang; Zhen Wu; Ya-meng He; Zu-run Yue (Advances in Materials Science and Engineering)
Artificially ground freezing method is increasingly applied in formations with high permeability. The groundwater seepage flow should be considered because an excessive groundwater seepage flow would make the merging of the frozen wall challenging. Therefore, in this study, we investigate the temperature field and frozen wall merging characteristics at varying groundwater seepage flow rates in gravel formation. Results show that the heat exchange between the seepage flow and freezing pipes delays the merging of the frozen wall and reduces its total thickness. The groundwater seepage flow restricts the freezing of the upstream zone and accelerates the freezing of the downstream zone. The upstream and downstream temperature fields are symmetrical in nonseepage flow conditions but are asymmetrical in the presence of seepage flow. The merged frozen wall presents an arched shape and shifts to the downstream zone. The “scouring effect” and “water barrier effect” simultaneously act on the merging process of the frozen wall. The total thickness of the frozen wall decreases by more than 30% when the flow rate increases from 0 to 5.0 m/d. Optimising the layout of the freezing pipes in gravel formations is a reasonable solution for a safe and economical design.